Molecular analysis and characterization of genes involved in glycogen storage disease type III and selected inherited metabolic disorders / Ili Syazwana Abdullah - Ili Syazwana , Abdullah (2019)
Inherited metabolic disorders (IMDs) comprise a wide range of diseases, and two groups, namely the glycogen storage diseases (GSDs) and methylmalonic aciduria (MMA) are the focus diseases in this study. Despite the fact that various genetic studies have been carried out and a mutation spectrum have been established in different populations worldwide, information on the genetic causes of these two categories of IMDs in the multi-ethnic Malaysian population is still lacking. In this study, a total of 27 patients were investigated, each suspected of having different types of glycogen storage diseases (namely GSD 1b, GSD III and FBS) or methylmalonic aciduria (MMA mut-type and MMA with homocystinuria cblC-type). Genomic DNA was extracted and the relevant genes were sequenced. Out of 27 patient samples, mutations were identified in 18 patients. In total, two different mutations were identified in the SLC37A4 gene (for GSD 1b patients), nine different mutations in the AGL gene (for GSD III patients), three different mutations in the SLC2A2 gene (for FBS patients), two different mutations in the MUT gene (for one MMA mut-type patient) and one mutation was observed in the MMACHC gene (for two MMA cblC-type patients). It is noteworthy that the c.2681+1G>A mutation previously reported to be commonly found for GSD III in Caucasian populations was also recurrently found in the Malay patients (n=7/22 alleles; 31.8%). Mutations that are yet unreported i.e. do not match any mutation in available databases were subjected to further analysis. However, due to time limitation, analysis of unreported mutations only focused on those causing GSD III. A total of six out of nine different mutations identified in GSD III patients were previously unreported (c.1423+1G>T, c.2914_2915delAA, c.3814_3815delAG, c.4333T>G, c.4490G>A, c.4531_4534delTGTC). Analyses using prediction software Human Splice Finder showed that the mutation c.1423+1G>T disrupts normal splicing motif, and in vitro assays later revealed that this mutation causes intron retention. Analyses on mutation c.2914_2915delAA, c.3814_ 3815delAG and c.4490G>A predict formation of truncated proteins and therefore not expected to retain normal protein function. The c.4333T>G substitution results in a missense mutation, and this Tyr to Asp amino acid substitution was predicted to be “damaging” using the Polyphen2 analysis software. The c.4531_4534delTGTC mutation on the other hand leads to a frameshift and codon read-through, resulting in a protein that is longer by 14 amino acids. It is important to note that all unreported mutations were absent in 150 healthy control samples, rejecting the possibility of them being mere polymorphisms. Findings of this study show that the mutation spectrum for GSD III Malaysian patients is heterogeneous but a common mutation for a specific ethnic group may be present. Information gathered in this study will be useful for future diagnosis efforts and subsequent administration of correct treatments. Moreover, the information obtained herein can be used for genetic counselling in families with history of inherited metabolic disorder.